Designing Early Warning System for The Impact of Industrial Development Waste by Using pH Control System - Sri Lestari, Veronika Nugraheni; Cahyono, Dwi; Susilowati, Sri (International Journal of Engineering and Technology, 2018)
Environment is inseparable from human life. Human negligence in building industry without caring the impact on environment can damage the physical and biological environment slowly and indirectly. Therefore an effort to preserve the quality of environment, especially for the environment adjacent to the settlement, is necessary and can be performed in various ways including technology utilization. Technology develops rapidly and electronic devices have become one compulsory device to be owned. Wastewater is industrial waste should be controlled prior to passing surrounding environment to avoid pollution. One way to control it is controlling its pH of, this is performed by early warning on pH level. This paper focused on designing control device for industrial waste water pH that is able to inform an early when on concentration of industrial waste water under normal limit water.
Keywords: Industry building; environment; microcontrollers; pH control.